Oncogenic role of miR‐155 in anaplastic large cell lymphoma lacking the t(2;5) translocation. Issue 4 (27th April 2015) - Merkel, Olaf; Hamacher, Frank; Griessl, Robert; Grabner, Lisa; Schiefer, Ana‐Iris; Prutsch, Nicole; Baer, Constance; Egger, Gerda; Schlederer, Michaela; Krenn, Peter William; Hartmann, Tanja Nicole; Simonitsch‐Klupp, Ingrid; et al.
Abstract Anaplastic large cell lymphoma (ALCL) is a rare, aggressive, non‐Hodgkin's lymphoma that is characterized by CD30 expression and disease onset in young patients. About half of ALCL patients bear the t(2;5)(p23;q35) translocation, which results in the formation of the nucleophosmin‐anaplastic lymphoma tyrosine kinase (NPM–ALK) fusion protein (ALCL ALK+). However, little is known about the molecular features and tumour drivers in ALK‐negative ALCL (ALCL ALK−), which is characterized by a worse prognosis. We found that ALCL ALK−, in contrast to ALCL ALK+, lymphomas display high miR‐155 expression. Consistent with this, we observed an inverse correlation between miR‐155 promoter methylation and miR‐155 expression in ALCL. However, no direct effect of the ALK kinase on miR‐155 levels was observed. Ago2 immunoprecipitation revealed miR‐155 as the most abundant miRNA, and enrichment of target mRNAs C/EBPβ and SOCS1. To investigate its function, we over‐expressed miR‐155 in ALCL ALK+ cell lines and demonstrated reduced levels of C/EBPβ and SOCS1. In murine engraftment models of ALCL ALK−, we showed that anti‐miR‐155 mimics are able to reduce tumour growth. This goes hand‐in‐hand with increased levels of cleaved caspase‐3 and high SOCS1 in these tumours, which leads to suppression of STAT3 signalling. Moreover, miR‐155 induces IL‐22 expression and suppresses the C/EBPβ target IL‐8. These data suggest that miR‐155 can act as a tumour driver in ALCL ALK− and blocking miR‐155 could be therapeutically relevant. Original miRNA array data are to be found in the supplementary material (Table S1). Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd